Double Prevention and Mental Causation - Johnson, Sean (2019)
Double prevention is often mentioned in the causation literature but is not often discussed in depth. In this thesis my primary goal is to take a deep look at double prevention and evaluate one place it has been put to work. Briefly, a case of double prevention is a case where one event prevents another from preventing a third. While we have strong intuitions that such cases should be causally relevant at least, there is debate over whether they should be counted as fully causal. Sophie Gibb (2013) puts this concept to work by arguing that mental events act as double preventers to physical events. She frames this as an argument against the causal exclusion problem. I propose my own adaption of Gibb’s proposal which does not rest on the controversial premises the original does and as such has a wider appeal.